089 Breaking the cycle of chronic daily headache with a low-dose subcutaneous lignocaine and ketamine infusion. (29th July 2019) - Rofe, Christopher JF; Garrick, Raymond; Burke, David; Brew, Bruce J; Tomlinson, Susan E
Abstract : Introduction: Management of chronic migraine includes correcting analgesic rebound headache and implementing suitable medication for prevention and acute episodes. However, in many cases this management paradigm oversimplifies the complexity of chronic migraine, particularly the entrenched central pathways that perpetuate chronic migraine. Intravenous lignocaine can curtail chronic migraine and analgesic rebound headache (1). Further, ketamine provides short-term analgesia and enables reduction in central sensitisation of pain pathways, particularly in the setting of codeine/opiod overuse (2). This paper describes use of subcutaneous lignocaine and ketamine infusion in chronic migraine. Methods: A prospective observational cohort study was undertaken in patients with chronic migraine. Patients received a prolonged subcutaneous lignocaine and ketamine infusion (mean duration 11 days) and underwent evaluation at four-time points over six months. The effects on the excitability of motor axons in the median nerve were documented using standard procedures. Results: Fourteen patients were recruited. The infusion was well tolerated; no major side effects were seen. There were no significant long-term changes in the excitability of motor axons. At six months, 13/14 patients had sustained benefit. Three of 4 patients remained free of analgesic rebound headache. One patient remained headache-free. Conversion to episodic migraine occurred in 6/14. Improvement in chronic migraine was reported by 6/14. Three of six were able to return to work, with 1 returning to studies. Benefit was greater in those with depression and history of opiod/codeine use. Conclusion: Subcutaneous lignocaine and ketamine can help break entrenchment in chronic migraine as part of a structured management plan.